2016
DOI: 10.1063/1.4962900
|View full text |Cite
|
Sign up to set email alerts
|

Design and demonstration of ultra-wide bandgap AlGaN tunnel junctions

Abstract: Ultra violet light emitting diodes (UV LEDs) face critical limitations in both the injection efficiency and light extraction efficiency due to the resistive and absorbing p-type contact layers. In this work, we investigate the design and application of polarization engineered tunnel junctions for ultra-wide bandgap AlGaN (Al mole fraction > 50%) materials towards highly efficient UV LEDs. We demonstrate that polarization-induced 3D charge is beneficial in reducing tunneling barriers especially for high composi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 36 publications
2
69
0
Order By: Relevance
“…Here, it is worth defining the polarization tunnel junction in which the polarization induced electric field in the polarization tunnel junction is along the same direction as the built‐in electric field, and thus the coupled electric field possesses the enhanced intensity. Zhang et al also demonstrate the polarization tunnel junction by studying the [0001] oriented n‐AlGaN/InGaN/p‐AlGaN . Recently, we have proposed and reported a n + ‐GaN/AlGaN/p + ‐GaN based tunnel junction for ultraviolet (UV) LEDs for which the n + ‐GaN/AlGaN/p + ‐GaN tunnel junction comprises a thin AlGaN layer to avoid absorbing the 380 nm UV photons .…”
Section: Introductionmentioning
confidence: 99%
“…Here, it is worth defining the polarization tunnel junction in which the polarization induced electric field in the polarization tunnel junction is along the same direction as the built‐in electric field, and thus the coupled electric field possesses the enhanced intensity. Zhang et al also demonstrate the polarization tunnel junction by studying the [0001] oriented n‐AlGaN/InGaN/p‐AlGaN . Recently, we have proposed and reported a n + ‐GaN/AlGaN/p + ‐GaN based tunnel junction for ultraviolet (UV) LEDs for which the n + ‐GaN/AlGaN/p + ‐GaN tunnel junction comprises a thin AlGaN layer to avoid absorbing the 380 nm UV photons .…”
Section: Introductionmentioning
confidence: 99%
“…10,11,13 Simulations further showed that efficient interband tunneling could be achieved for high Al content AlGaN by using a compositionally graded tunnel junction structure. 12 It demonstrated the feasibility of achieving tunneling hole injection into deep UV LEDs.…”
mentioning
confidence: 97%
“…The structure was grown by N 2 plasma assisted molecular beam epitaxy (MBE) on Si-doped metal-polar Al 0.72 Ga 0.28 N template with a threading dislocation density of 3×10 9 cm -2 . [10][11][12][13] The template was grown on sapphire substrate using metal-organic chemical vapor deposition (MOCVD). The MBE growth was layer.…”
mentioning
confidence: 99%
“…Another benefit of the tunnel-injected UV LED structure is that holes are injected through interband tunneling, which resists the influence of the extremely low thermal activation rate of Mg acceptors in AlGaN. 17,18 This is critical for deep UV LEDs, as the thermally activated hole concentration decreases significantly with the increasing Al content in the p-AlGaN layer. While conventional UV LEDs have encountered a substantial efficiency reduction when lowering the emission wavelength in the deep UV wavelength range, the tunnel-injected UV LED structure could potently solve the problem and lead to efficient deep UV emitters.…”
mentioning
confidence: 99%